Year 7 students use of three-dimensional modelling while designing and making - Malcolm Welch (1997)
The study described here investigated assumptions in the literature about how students model ideas while designing and making. Additionally, it investigated protocol analysis as a methodology for the analysis of designers' strategies. Five Year 7 dyads were video recorded while completing a design and make task. Analysis involved transcribing and segmenting the conversation between subjects and then adding to the protocols a description of their actions. Each period of action was coded and the coded transcripts analysed. Analysis made evident five significant differences between modelling as described in the literature and as used by subjects. First, three-dimensional modelling largely replaced two-dimensional modelling. Second, subjects developed solutions serially rather than producing several solutions at the outset. Third, three-dimensional modelling was used to manifest not only existing ideas but to fuel new ideas. Fourth, modelling was used to develop and also to refine ideas. Fifth, models were evaluated not only upon completion but from the moment that designing and making began. These results suggest it is important to provide students, early in the process of designing and making, an opportunity to explore, develop and communicate their design proposals by modelling ideas in three-dimensional form.